Proneness to formation of tight and rigid fibrin gel structures in men with myocardial infarction at a young age. - Fatah, K; Silveira, A; Tornvall, P; Karpe, F; Blombäck, M; Hamsten, A (1996)
The native fibrin gel structure formed in vitro from plasma samples was examined by liquid permeation of hydrated fibrin gel networks in 38 unselected men who had suffered a myocardial infarction before the age of 45 years and in 88 age-matched population-based control men. Both the fibrin gel porosity (permeability coefficient, Ks) and the calculated fiber mass-length ratio varied considerably within the two groups, but were generally lower in the patients. Ks was 8.3 +/- 5.2 cm2 x 10(9) (mean +/- SD) in the patient group and 12.5 +/- 5.7 cm2 x 10(9) among controls (p < 0.001). The corresponding figures for fiber mass-length ratio were 13.1 +/- 7.7 and 16.5 +/- 7.5 Dalton/ cm x 10(-13), respectively (p < 0.01). Around 50% of the patients had Ks values below the 10th percentile of the control group. A strong inverse correlation was seen between plasma plasminogen activator inhibitor-1 (PAI-1) activity and Ks (r = -0.603, p < 0.001) or fiber mass-length ratio (r = -0.565, p < 0.001) in the patient group. Corresponding weaker associations of PAI-1 with fibrin gel properties were also present in the control group. In addition, inverse relationships of very low density lipoprotein (VLDL) triglyceride concentrations to Ks (r = -0.362, p < 0.001) and fiber mass-length ratio (r = -0.283, p < 0.01) were found among the controls. Proneness to formation of tight and rigid fibrin gel networks with abnormal architecture in vitro is in vivo associated with myocardial infarction at a young age. Impaired fibrinolytic function secondary to a raised plasma PAI-1 activity level is associated with abnormal fibrin gel structure.